EXPERIMENTAL ANALYSIS OF USING EXAMPLE-NONEXAMPLE METHOD IN INCREASING STUDENTS' READING SKILLS - Ayu Fardillah; Maya Agustina; Nurul Hidayah (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
This research aims to enhance the reading ability of students at MIN 21 Meulaboh by implementing the Examples and Non-Examples method. It is a quasi-experimental study with a one-group pre-test and post-test design. The population of this study consists of 16 students in the second grade of MIN 21 Meulaboh. Data collection techniques include observation sheets for student activities, teacher observations, and pre-test and post-test assessments. The data analysis results before applying the Examples and Non-Examples method showed that students' reading ability obtained an average score of 79.68. After applying the Examples and Non-Examples model, the average score increased to 92.81. The hypothesis testing results for the second-grade students showed a calculated t-value greater than the critical t-value (24.75 > 1.75), indicating the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha). These findings demonstrate the influence of implementing the Examples and Non-Examples model in improving students' reading ability at MIN 21 West Aceh